2020
DOI: 10.1007/s10900-020-00849-1
|View full text |Cite
|
Sign up to set email alerts
|

Telephone or Visit-Based Community Health Worker Care Management for Uncontrolled Diabetes Mellitus: A Longitudinal Study

Abstract: Community health workers (CHWs) can reduce health disparities for low income patients but type of contact and outcomes has had limited study. Low-income Hispanic primary care patients with hemoglobin A1c [HbA1c] ≥ 9% received care managment (CM) over 6 months classified as: (CM1) telephone only; (CM2) clinic visit but no calls; (CM3) clinic visit with calls; and (CM4) ≥ 2 visits ± calls. Type of CM delivery and time to DM control (HbA1c < 9%) examined in Cox proportional hazards model and more rapid control wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…In-person contacts between the client and the CHW thus appear to positively influence the client's ability to address health, social, and behavioral risk factors, in comparison to other forms of contact including phone calls, emails, text messages, and faxing. While other studies have found positive effects of CHW in-person engagement among vulnerable patients with specific chronic diseases, 17,34,41 this study suggests that the beneficial impacts of in-person engagement extend to broader measures of risk-reduction across multiple health-related indicators as well as specific chronic disease conditions.…”
Section: Discussioncontrasting
confidence: 63%
“…In-person contacts between the client and the CHW thus appear to positively influence the client's ability to address health, social, and behavioral risk factors, in comparison to other forms of contact including phone calls, emails, text messages, and faxing. While other studies have found positive effects of CHW in-person engagement among vulnerable patients with specific chronic diseases, 17,34,41 this study suggests that the beneficial impacts of in-person engagement extend to broader measures of risk-reduction across multiple health-related indicators as well as specific chronic disease conditions.…”
Section: Discussioncontrasting
confidence: 63%
“…Therefore, older patients or patients with difficulties in using technology may have been more affected by this forced change towards telehealth, as described elsewhere [28] , [29] . One study performed in uncontrolled diabetes mellitus patients in late 2020 showed that T2DM control was less likely to be achieved by telephone only compared to face-to-face visits and suggested that to benefit vulnerable patients with uncontrolled T2DM, in-person engagement may be required [30] . This is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The type of care that CHWs provide varies in effectiveness as well. For instance, in a pilot project for Texas’ Transformation and Quality Improvement Program, the Texas Department of Health and Human Services certified CHWs to work with patients with diabetes [ 37 ]. Blood sugar control was more rapid in patients who received in-person care from CHWs compared to patients who participated in telehealth with CHWs [ 37 ].…”
Section: Resultsmentioning
confidence: 99%